Democratic accountability and the use of force in international law - Ku, Charlotte, 1950-; Jacobson, Harold Karan (Cambridge University Press, 2003)
"This book explores the experiences of nine countries (Canada, France, Germany, India, Japan, Norway, Russia, the United Kingdom, and the United States) in the deployment of armed forces under the UN and NATO, asking who has been and should be accountable to the citizens of these nations, and to the citizens of states who are the object of deployments, for the decisions made in such military actions. The authors conclude that national-level mechanisms have been most important in ensuring democratic accountability of national and international decision-makers."--Jacket